Determinants of Tobacco Consumption in Papua New Guinea : Challenges in Changing Behaviors - Hou, Xiaohui (World Bank, Washington, DC, 2015)
This paper analyzes smoking prevalence and smoking behaviors in Papua New Guinea. Using the 2009–10 Papua New Guinea Household Income and Expenditure Survey, the paper analyzes the determinants of tobacco use and tobacco choices in Papua New Guinea. The results show that adults (18 years and above) in the poorest quartile are more likely to smoke. Tobacco consumption imposes a large financial burden to poor households. Tobacco consumption accounts for about 23 percent of total household food expenditure for households in the poorest quartile, compared with 15 percent for the entire sample. However, most of these households consume non-processed tobacco. The study reveals the urgency to control tobacco consumption in Papua New Guinea and considers some practical challenges that the country may face.